Entrepreneurship motivation among UTM technical and non technical undergraduate students. - Koe, Wei Loon (2004)

(untitled)
ABSTRACT This study examined the motivation for entrepreneurship among UTM technical and non-technical undergraduate students. Past literatures suggested that a student who is motivated for entrepreneurship will show stronger intention to start up own business or enterprise than an unmotivated student. Therefore, this study looked at the four motivational factors: (1) Life experience, (2) Entrepreneurship education, (3) Environment, and (4) Personal characteristics; to examine the level of motivation among UTM students and to test whether there exist significant differences in motivational level between UTM technical and non-technical students. The study also focused on the issue of students’ intention to start up own business or enterprise. Questionnaires were used to collect the data on students’ motivational and intention level. Subsequently, Mann-Whitney U test was conducted to determine if any significant differences exist on the motivational factors and intention level between technical and non-technical students. The results of this study indicated that students were motivated by life experience, entrepreneurship education, environment and personal characteristics for entrepreneurship. No significant difference was found in entrepreneurship education between technical and non-technical students for entrepreneurship. However, significant differences were found in life experience, environment and personal characteristics between technical and non-technical students. Furthermore, students were also considering to start up own business or enterprise. Several recommendations emerged from the analysis of the findings. It is believed that these recommendations are useful for university, government as well as public wishing to improve the development of entrepreneurs, especially among the young ones. vi